Slogans Subjection, Subversion, and the Politics of Neoliberalism - Makovicky, Nicolette; Trémon, Anne-Christine; Zandonai, Sheyla S. (Routledge Studies in Anthropology, 2019)
Focusing on contexts of accelerated economic and political reform, this volume critically examines the role of slogans in the contemporary projects of populist mobilization, neoliberal governance, and civic subversion. Bringing together a collection of ethnographic studies from Greece, Slovakia, Poland, Abu Dhabi, Peru, and China, the contributors analyze the way in which slogans both convey and contest the values and norms that lie at the core of hegemonic political economic projects and ideologies.